Workshop Pemodelan Matematika sebagai Upaya untuk Meningkatkan Kemampuan Matematis Mahasiswa - Noraniza Bahrotul Ilmi; Ratri Candra Hastari (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Mathematical modeling is an essential skill that supports students' problem-solving and critical thinking abilities. However, initial observation results indicate that most students still have difficulty understanding the concepts and steps of modeling systematically. Based on these findings, the mathematical modeling workshop was held with the aim of improving participants' understanding thru material delivery and interactive Q&A sessions. Data collection methods include observation of participant engagement and questionnaires to assess participants' perceptions of material clarity, relevance, and improved understanding. The analysis was conducted using a descriptive qualitative and quantitative approach. The results of the activity show enthusiasm and engagement from the participants, as well as a positive response to the material presented. As many as 78% of the participants stated that there was an increase in their understanding of mathematical modeling. Overall, this workshop was able to have a positive impact on participants' understanding of mathematical modeling and serve as a foundation for future activities.